Avaliação de desempenho de serviços emergenciais de saúde em redes sem fio heterogêneas - Oliveira, Marcelino Nascimento de (2014)
The health applications aimed at monitoring patients remotely have reached great proportions with the advancement of wireless networks. This paper presents a study of performance evaluation of biosignal traffic, which was simulated the transmission of patient data in emergency situations. The simulation scenario considered the transmission of signals from an ambulance through wireless network and collected in a medical monitoring center. On the way to the hospital, while the mobile broadcast biosignals moved between areas covered by different network technologies, featuring vertical handover situation. Based on the minimum QoS requirements prevailing in the scientific community, the most important parameters in healthcare applications such as loss rate, delay, throughput and jitter were evaluated. Was still considered a minimum bandwidth required for transmission of vital signs, taking into account rates of known samples to physicians signs such as electrocardiogram (ECG), blood pressure, heart rate, body temperature and rate of oxygen saturation blood. To evaluate the performance, were carried computer simulations using an implementation of the IEEE 802.21 standard for the simulator NS-2. The simulated scenario used the networks of Wi-Fi and WiMAX technologies, mobile with multiple interfaces and nodes cargo, which made transmissions with constant rates. The results showed that the network technologies in use can meet the minimum QoS requirements for medical applications.